PENGARUH MOTIVASI KARYAWAN TERHADAP PENINGKATAN PELAYANAN KONSUMEN PADA TOKO BUKU FAJAR AGUNG DI BANDAR LAMPUNG - Nuzleha - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
Research purposes is to know the influence of motivation employees to increasing servicesto customers in a bookstore fajar the great in lampung. hypothesis researchers is motivationemployees have leverage to increasing consumer service at Fajar Agung bookstore.Samples was 40 employees both men and women have equal opportunities as (population).A method of analysis of qualitative and quantitative using formulas correlation product moment theresults of the quantitative analysis of reckoning statistics obtained as follows: that r count = 0,504,then compared with the value of r table product moment in n = 40 using standard significant 5 % =0,312 and first significant 1 % = 0,396, it turns out that comparison is indicated r count = 0,504 % rtable; 0,312 and 0,396. It is concluded that hypothesis, namely motivation employees influentialfavorably to an increase in customer service in a shop fajar the great in lampung, acceptable. Nextafter compared to the criteria of measurement koreasi where r count = 0,504 situated between 0,71 -- 90,00 with criteria high.